Superstrate-integrated switchable beam rectangular microstrip antenna for gain enhancement - Kawdungta, Supakit; Jaibanauem, Puwanai; Pongga, Rattiya; Phongcharoenpanich, Chuwong (My University, 2017)
This research has proposed a switchable beam rectangular microstrip antenna with double parasitic patches, in which two PIN diodes were deployed for manipulation of the main beam direction and a superstrate (i.e. Either a dielectric slab or metamaterial) for enhancement of the antenna gain. The dielectric slab is a second FR4 substrate while the metamaterial (MTM) is the 7 × 17 periodic structure of planar cycloid dipoles (PCD). Simulations were carried out and three different antenna prototypes (i.e. The proposed switchable beam rectangular microstrip antenna, the proposed antenna either with dielectric slab or MTM) fabricated and experimented. The simulation and experimental results are in good agreement and exhibit good impedance matching (|S11| <-10 dB) along the operating frequency. The average measured gain is 7 dBi with the unidirectional radiation pattern along the operating frequency. The proposed switchable antennas with and without the superstrate are operable in the 2.4-2.5 GHz WLAN system and switchable in three directions of 0°, 30° and 330° (xy-plane). Moreover, the findings validate the applicability of either the dielectric slab or three MTM block-layers as the superstrate to improve the antenna gain.
Keywords: Gain enhancement; Metamaterial; Microstrip; Parasitic patch; PIN diode; Superstrate; Switched beam